Dystonic Pseudo Foot Drop. Issue 3 (9th May 2015) - Aquino, Camila C.; Slow, Elizabeth; Lang, Anthony E.
Abstract: The most common presentation of foot dystonia in patients with Parkinson's disease (PD) or dystonia is inversion of the foot accompanied by flexion of the toes, with or without extension of the hallux. Less commonly, foot dystonia may mimic foot drop, as occurs with weakness of the dorsiflexors muscles, resulting in a pseudo foot drop. This has rarely been reported in the literature and has been poorly recognized, often leading to misdiagnosis and unnecessary investigations and treatment. We report 5 patients with dystonic pseudo foot drop, one of them diagnosed with early‐onset PD, 2 with sporadic PD, and 2 with dystonia. Despite the steppage gait, their physical exam revealed normal strength, and no other explanation for a "foot drop" was found. It is important to recognize this phenomenology, which can be a clue to the diagnosis of early‐onset PD, and may be responsive to levodopa in selected patients.